Derajat Otonomi Fiskal Daerah Kabupaten Bangka Barat - Pebri Harto; Intiyas Utami; Rulyanti Susi Wardhani (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine and analyze the Degree of Autonomy/Fiscal Independence in West Bangka Regency and analyze how big the correlation between GRDP and PAD is in West Bangka Regency. This study uses a quantitative approach with data analysis methods and hypothesis testing using panel data regression analysis. The data used in this research is the Regional Finance data of West Bangka Regency and the GRDP of West Bangka Regency in 2011 - 2020. The results of the study show that the value of the Degree of Fiscal Autonomy (DOF) of West Bangka Regency in the period 2011 to 2020 with the category " very less” but despite having a relatively small PAD, the GRDP of West Bangka Regency has always experienced growth, especially in the Manufacturing Sector, namely the tin processing industry. Based on the results of the analysis, the correlation value between GRDP and PAD is negative, meaning that the relationship between the two variables is not in the same direction, thus it can be interpreted that although PAD increases, GRDP has decreased. This is due to the fact that GRDP is dominated by the manufacturing sector which has no effect on local revenue. Because the processing sector is controlled by BUMN, namely PT. Timah Tbk.